2016
DOI: 10.12966/abc.01.05.2016
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and Nocturnal Activity Time Budgets of Asian Elephants (Elephas maximus) in a Zoological Park

Abstract: -The diurnal and nocturnal activity time budgets of five adult female Asian elephants (Elephas maximus)were studied in a zoological park for two 24-hour, five 14-hour, and one 9-hour observation periods between May and June 2011. Relatively few studies have looked at detailed daytime and nighttime activity time budgets in captive Asian elephants. Continuous observation was used to measure the activity time budgets of at least one focal animal per observation period. The activity time budgets varied between ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 22 publications
3
16
0
Order By: Relevance
“…However, there was also individual variability observed between the bulls. These responses are comparable to research monitoring behavioural changes in zoo and circus elephants after they were removed from tethers (e.g., [ 15 , 44 , 45 ]).…”
Section: Discussionsupporting
confidence: 75%
“…However, there was also individual variability observed between the bulls. These responses are comparable to research monitoring behavioural changes in zoo and circus elephants after they were removed from tethers (e.g., [ 15 , 44 , 45 ]).…”
Section: Discussionsupporting
confidence: 75%
“…Parker et al 2020 ). While data on nocturnal activity of elephants is limited, and largely focused on fully captive systems, there is some evidence that elephants may be stationary for large periods of the night (Wilson et al 2006 ; Lukacs et al 2016 ), and that activity depends on age and access to outside areas (Evison et al 2020 ) suggesting that most social activity takes place during diurnal hours. The measures of elephant sociality used in our study might have been too broad to capture any potential weak infection–sociality associations present in our study population or actually not capture specific social–infection mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Her average of 219·5 minutes per night is at the lower end of the sleep times recorded by other studies; however, it is still within normal parameters. Lukacs et al () reported Asian elephant calves lying down between 0 and 45% (0 to c. 324 minutes) of the night, with an average of 13% ( c. 94 minutes). At Night Safari sleep time varied from as little as 25 minutes to as much as 390 minutes.…”
Section: Discussionmentioning
confidence: 99%